ASSESSMENT OF THE IMPACT OF TIDES, STORM SURGES TO THE RIVER SYSTEM BY 1-2D MODELING - Kien, Nguyen Chinh; Manh, Dinh Van; Co, Nguyen Thanh (Vietnam Journal of Marine Science and Technology, 2014)
Vietnam has a system of 392 rivers, which run into the sea through 114 estuaries and inlets from the North to the South, and there is one estuary every 23km averagely. The economic and tourism activities etc. are very active ni the estuaries. However, the hydrodynamic processes included the interaction of tides, storm surges and river flow are very complex in these estuaries . In this study a linked 1D and 2D software has been implemented to investigate some properties of long waves (tides, storm surges) in the interactions with river flow to assess the impact of tides, storm surges to the lower sections of river.